ANALISIS VEGETASI DI KAWASAN SEMPADAN EMBUNG BUAL, DESA AIK BUAL KECAMATAN KOPANG KABUPATEN LOMBOK TENGAH - Diah Permata Sari; Kornelia Webliana B; Maiser Syaputra (Forestry Study Program University Of Mataram, 2019)
Embung Bual is one of the tourist attraction objects in Lombok Tengah Regency. Vegetation analysis in the border area of Embung Bual is necessary to know dan to identify the structure and composition of vegetation in the border area of Embung Bual because vegetation is an important elemen in water conservation efforts. This study aims to analyze the structure and composition by analyzing the importance value index and diversity index in the border area of Embung Bual. Vegetation in the border area of Embung Bual was analyzed by using the striped path method with nested quadrats. The vegetation data obtained were carried out with an importance value index (INP) and diversity index. The results showed that the Embung Bual border area was dominated by Mahogany species at the tree life phase with an INP value of 60.21%, the pole life phase was dominated by Cempaka species with an INP value of 74.36%, at the sapling phase was dominated by Kumbi with INP value 55,09% and the seedling life phase was dominated by Mahogany species with an INP value of 88.54%. Embung Bual border area has a composition of 22 species and has a Simpson diversity index with a value of 0.86 which is included in the high category, and has a Shannon diversity index with a value of 2.43 which is included in the high category